Battery Management System for Electric Vehicles with Charge Monitoring and Fire Protection - Landge Pradip; Bhujbal Rohan; Chavan Shahaji; Mhaske Shubham; Prof. Avchat Harish (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Battery storage is vital for the functioning of electric vehicles (EVs), as it holds the energy required for their operation. Therefore, to maximize battery output and ensure safe operation, an efficient battery management system (BMS) is indispensable. The BMS monitors various parameters, calculates State of Charge (SoC), and offers necessary services to guarantee the battery’s safety. It plays an integral role in EVs, safeguarding both users and batteries by ensuring the cells operate within safe parameters. The proposed system not only monitors and charges the battery safely but also prevents accidents. Its functions include current and voltage measurement, SoC calculation, protection mechanisms, battery status detection, and a liquid crystal display (LCD). Electric vehicles (EVs) utilize electric motors and rechargeable batteries instead of internal combustion engines (ICEs) fueled by fossil fuels. A BMS is crucial for EVs and other battery-powered systems, overseeing and regulating the battery pack’s operation to optimize performance, safety, and lifespan. State of Charge (SoC) indicates the remaining energy in a battery as a percentage of its total capacity, allowing users to estimate remaining range or usage time before recharging is necessary.